The Next Decade of Seismic Oceanography: Possibilities, Challenges and Solutions - Dickinson, Alex; Gunn, Kathryn L. (Frontiers in Marine Science, 2022)
Seismic reflection profiling of thermohaline structure has the potential to transform our understanding of oceanic mixing and circulation. This profiling, which is known as seismic oceanography, yields acoustic images that extend from the sea surface to the sea bed and which span horizontal distances of hundreds of kilometers. Changes in temperature and salinity are detected in two, and sometimes three, dimensions at spatial resolutions of ~ O(10) m. Due to its unique combination of extensive coverage and high spatial resolution, seismic oceanography is ideally placed to characterize the processes that sustain oceanic circulation by transferring energy between basin-scale currents and turbulent flow. To date, more than one hundred research papers have exploited seismic oceanographic data to gain insight into phenomena as varied as eddy formation, internal waves, and turbulent mixing. However, despite its promise, seismic oceanography suffers from three practical disadvantages that have slowed its development into a widely accepted tool. First, acquisition of high-quality data is expensive and logistically challenging. Second, it has proven difficult to obtain independent observational constraints that can be used to benchmark seismic oceanographic results. Third, computational workflows have not been standardized and made widely available. In addition to these practical challenges, the field has struggled to identify pressing scientific questions that it can systematically address. It thus remains a curiosity to many oceanographers. We suggest ways in which the practical challenges can be addressed through development of shared resources, and outline how these resources can be used to tackle important problems in physical oceanography. With this collaborative approach, seismic oceanography can become a key member of the next generation of methods for observing the ocean.